ANALISIS HARGA DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN (STUDI KASUS PADA GROSIR FERRY DI PASIR PENGARAIAN) - Vevu Lestari Putri Gulo; Heffi Christya Rahayu; Ratna Dewi (Jurnal Ekonomi Bisnis Kompetif, 2026)
This study aims to analyze the influence of price and product quality on consumer purchasing interest at Grosir Ferry in Pasir Pengaraian. Increasingly tight competition in the grocery retail business requires businesses to set appropriate prices and maintain product quality to attract and maintain consumer purchasing interest. This study uses a quantitative approach with a survey method. The research sample consisted of 97 respondents who were Grosir Ferry consumers. Data were collected through a questionnaire with a Likert scale and analyzed using multiple linear regression analysis with the help of the SPSS program. Data testing included validity tests, reliability tests, classical assumption tests, coefficient of determination tests, and partial and simultaneous hypothesis tests. The results of the study indicate that price influences consumer purchasing interest, product quality influences consumer purchasing interest, and price and product quality simultaneously have a significant effect on consumer purchasing interest at Grosir Ferry in Pasir Pengaraian. The results of this study indicate that appropriate pricing and maintained product quality can increase consumer purchasing interest. This study is expected to be a consideration for Grosir Ferry managers in developing pricing strategies and improving product quality to increase consumer purchasing interest.